RISK BASED ASSESSMENT FRAMEWORK FOR MAINTENANCE OF AGEING REINFORCED CONCRETE STRUCTURES ON ONSHORE PROCESS PLANTS - BABA, HAMMAD DABO (2018)
Oil and gas industry is an important industry that contributes significant source of earning for many countries. Whilst, process plants are engineering systems in to which oil and gas are processed, stored, and distributed for local consumption and exports.